Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

MXene hollow microspheres with tunable sizes and heterostructures for high-efficiency broadband microwave absorption - Yan-Qin Wang; Lin Zhang; Hao Chen; Zi-Hao Wang; Fu-Rong Zeng; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Crop-livestock system based on legume intercropping improves forage productivity, Tibetan sheep performance, and economic returns for farmers and herders: A regional integrated planting-feeding study - Chong Liang Luo; Hai-Xia Duan; Yong-Wei Chen; Mushtaq Ahmad; Xue-Ping Han; Hong-Jin Liu; Yong-Rong Fang; Fazal Ullah; Shi-Xiao Xu (European Journal of Agronomy, 2026)

A dual-function electroactive hydrogel platform for mitigating oxidative stress and restoring muscle function - Yi Lin; Zi-Hao Lin; Hai-Bin Jiang; Yu-Hao Kang; Qing-Song Deng; Rong-Tai Zuo; Zhi-Qi Lin; Er-Peng Yang; Jun-Jie Xu; Clara Chen; Xi-Ming Wang; Jin-Zhong Zhao (Chemical Engineering Journal, 2026)

In-situ generation and activation of H2O2 by synergistic dipole moment and multi-metal cycle for piezo-photocatalytic water cleanup - Zheng-Tao Dong; Long Sui; You Wu; Xiao-Ju Wen; Ya-Ya Yang; Yan-Rong Chen; Wen-Jun Wang; Hai Guo (Chemical Engineering Journal, 2026)

Oxygen mass transfer characteristics of different hollow-fiber bubble-free aeration membranes via clean water oxygenation tests under different aeration and measurement modes - Zhe Yuan; Chun-Hai Wei; Jing-Su Liu; Zhi-Wei Lian; Jing-Yin Wang; Hua-Rong Yu; Hong-Wei Rong; Zhi-Hui Pan; Zhong-Lin Nie; Ya-Song Chen; Xia Huang (Water Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Phosphorus–boron synergistic carbonization/dormancy strategy enables polyurethane foams with aging enhanced fire safety - Shuang Li; Hai-Bo Zhao; Ming-Jun Chen; Lei He; Lin Zhang; Fu-Rong Zeng; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Interfacial engineering of core-shell Cu@Zn nanoclusters enables methane selective CO2 electroreduction via accelerated water dissociation - Wenlong Cao; Caiyu Chen; Hai Liu; Lei Yang; Tianlong Tan; Ruiyang Xu; Chengjian Ma; Tianyu Wang; Daniel Hedman; Shigeo Maruyama; Rong Xiang; Jue Wang; et al. (Chemical Engineering Journal, 2026)

Global meta-analysis reveals nutrient-dependent symbiosis: Perennial legumes gain microbial advantages under nitrogen/phosphorus enrichment - Hai-Xia Duan; Chong-Liang Luo; Muhammad Maqsood Ur Rehman; Sheng-Rong Chen; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2026)

An intelligent multi-stage fishway integrating computer vision and adaptive hydraulic control - Guiwen Rong; Tengyu Ma; Hongling Jiang; Shangzhi Chen; Yangyan Zhang; Guoqing Zhao; Hai Lin; Huaiqin Ran (Ecological Engineering, 2026)

Sorption and degradation of α-terpineol in soils with distinct physicochemical properties - Huan-Feng Chen; Zi-Jun Yang; Hai-Rong Chen; Hai-Ming Zhao; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Lei Xiang (Environmental Geochemistry and Health, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

One new rearranged pyranone derivative with antibacterial activity from Xylaria curta YSJ-5 - Shan-Shan Wei; Dao-Jun Rong; Jia-Ying Lai; Chen Chen; Si-Ran Li; Zhong-Hua Yu; Hai-Bo Tan (Phytochemistry Letters, 2025)

Freshwater flux-induced salinity effect on ENSO in the tropical Pacific under global warming - Hai Zhi; Jiahao Chen; Rong-Hua Zhang; Minmin Wu; Jiaxiang Gao; Lu-Ying Yin (Climate Dynamics, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

The synergistic enhancement of adsorption for Pb2+ and organic dyes by a chitosan-based hydrogel as a multipollutant adsorbent - Yun Wang; Li-Ping Fang; Chen-Yang Li; Chang-Jing Cheng; Ting Liang; Xing-Bin Lv; Hai-Rong Yu (Journal of Environmental Chemical Engineering, 2025)

One-pot strategy for multifunctional recyclable thermally conductive phase change composites toward efficient thermal management - Yunfang Li; Rong Zhang; Baokuan Zhou; Chenxi Liu; Xudong Fu; Hai Chen; Qingting Liu; Shengfei Hu (Chemical Engineering Journal, 2025)

AHNAK2 Regulates NF-κB/MMP-9 Signaling to Promote Pancreatic Cancer Progression - Na-na Tang; Rong-bo Xu; Bo Jiang; Hai-ling Zhang; Xiao-song Wang; Dan-dan Chen; Ji-jun Zhu (Biochemical Genetics, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Variation in climate and hydrological conditions in Southwest China during the mid-to-late Holocene, inferred from stalagmite multiple proxies - Hua-Yan Li; Yao Wu; Ting-Yong Li; Rong Duan; Hai-Bo Wang; Jia-Hui Cui; Chao-Jun Chen; Yue Jin; Yue-Hua Xiang; Zi-Qi Liu; Jun-Yun Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Recruitment of copiotrophic and autotrophic bacteria by hyperaccumulators enhances nutrient cycling to reclaim degraded soils at abandoned rare earth elements mining sites - Yong-He Han; Xi-Wen Cui; Hai-Yan Wang; Xiao-Bin Lai; Ying Zhu; Jia-Bing Li; Rong-Rong Xie; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

Simultaneous recovery of water and antiscalant from cooling tower blowdown water by electrodialysis: Mechanism and cost-effectiveness - Jia-Rong Li; Jing-Han Wei; Yu-Chen Jin; Xian-Qiu Zhang; Hai-Ou Song; Ming-Xia Du (Journal of Cleaner Production, 2025)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Isobavachin induces autophagy-mediated cytotoxicity in AML12 cells via AMPK and PI3K/Akt/mTOR pathways - Ning Xia; Qing-Hai Chen; Zhao-Jun Meng; Shu-Yue Ma; Jia-Li Huang; Rong Shen; Yu-Tong Dong; Hai-Wei Du; Kun Zhou (Toxicology in Vitro, 2024)

Microplastics footprint in nature reserves-a case study on the microplastics in the guano from Yancheng Wetland Rare Birds National Nature Reserve, China - Huimin Jiang; Hai Cheng; Shiyue Wu; Hongshan Li; Hao Chen; Zhenghao Li; Xinyun Yao; Yanan Zhang; Yaqin Chen; Shuyi Chen; Shihao Chen; Liang Zheng; et al. (Environmental Research, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Neuroglobin Facilitates Neuronal Oxygenation through Tropic Migration under Hypoxia or Anemia in Rat: How Does the Brain Breathe? - Chun-Yang Li; Hai-Feng Jiang; Li Li; Xiao-Jing Lai; Qian-Rong Liu; Shang-Bin Yu; Cheng-La Yi; Xiao-Qian Chen (Neuroscience Bulletin, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Effects of scale and contrast of spatial heterogeneity in plant-soil feedbacks on plant growth - Lin Huang; Rong-Yi Chen; Wei Xue; Fei-Hai Yu (Science of The Total Environment, 2023)

Mechanism of polycyclic aromatic hydrocarbons degradation in the rhizosphere of Phragmites australis: Organic acid co-metabolism, iron-driven, and microbial response - Ni-chen Zhang; Dan A; Yuan-qing Chao; Hai-Yan Li; Charles Li; Qing-qi Lin; Ya-ying Li; Rong-liang Qiu (Environmental Pollution, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

Karst-ecological changes during the middle and late Holocene in Southwest China revealed by δ18O and δ13C records in a stalagmite - Rong Duan; Ting-Yong Li; Jun-Yun Li; Christoph Spötl; Hong-Chun Li; Hai-Bo Wang; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Jing-Li Zhou; Chao-Jun Chen; Tsai-Luen Yu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Changes in cropland soil carbon through improved management practices in China: A meta-analysis - Bai-Jian Lin; Ruo-Chen Li; Mu-Yu Yang; Zheng-Rong Kan; Ahmad Latif Virk; Yves N′Dri Bohoussou; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Journal of Environmental Management, 2023)

Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis - Rong-Zhen Liang; Cong Luo; Yuan Liu; Wan-Li Hu; Yi-Hang Guo; Hai-Xia Yu; Ting-Ting Lu; Shu-Quan Chen; Xiu-Juan Zhang; Xin-Hua He (Plant Science, 2023)

Eudesmane−type sesquiterpenes from the rhizomes of Atractylodes macrocephala and their bioactivities - Hai-Xin Zhang; Jin-Guang Si; Jing-Rong Li; Meng Yu; Ling-Ling Qin; Chen-Xu Zhao; Tao Zhang; Zhong-Mei Zou (Phytochemistry, 2023)

Carbonate nanophase guided by terminally functionalized polyisoprene leading to a super tough, recyclable and transparent rubber - Mo-Kun Chen; Yi-Hai Zhao; Rong Zhang; Ying Yang; Jian Cao; Mao-Zhu Tang; Guangsu Huang; Yun-Xiang Xu (Chemical Engineering Journal, 2023)

Three new C 21 steroidal glycosides isolated from Metaplexis japonica and their potential inhibitory effects on tyrosine protein kinases - Xu Wang; Qing-Yun Ma; Chen Liu; Jia Yang; Qing-Tao Lv; Zhen-Hua Tian; Hai-Qiang Jiang; Rong Rong (Natural Product Research, 2022)

Phenolic glycosides and flavonoids with antioxidant and anticancer activities from Desmodium caudatum - Qian-Nan Xu; Dan Zhu; Guang-Hui Wang; Ting Lin; Cui-Ling Sun; Rong Ding; Wen-Jing Tian; Hai-Feng Chen (Natural Product Research, 2021)

Emerging role of air pollution in chronic kidney disease - Yue Chen; Fan Cao; Jian-Ping Xiao; Xin-Yu Fang; Xue-Rong Wang; Li-Hong Ding; De-Guang Wang; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Biocontrol mechanism of Myxococcus fulvus B25-I-3 against Phytophthora infestans and its control efficiency on potato late blight - Zhi Hua Wu; Qiang Ma; Zhi Ning Sun; Hai Chen Cui; Hui Rong Liu (Folia Microbiologica, 2021)

Crosstalk between PKC and MAPK pathway activation in cardiac fibroblasts in a rat model of atrial fibrillation - Wei-hua Guo; Xian Wang; Mei-sheng Shang; Zhe Chen; Qi Guo; Li Li; Hai-ying Wang; Rong-hui Yu; Chang-sheng Ma (Biotechnology Letters, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Two new benzophenones and one new natural amide alkaloid isolated from a mangrove-derived Fungus Penicillium citrinum - Cai-Juan Zheng; Hai-Xia Liao; Rong-Qing Mei; Guo-Lei Huang; Lu-Jia Yang; Xue-Ming Zhou; Tai-Ming Shao; Guang-Ying Chen; Chang-Yun Wang (Natural Product Research, 2019)

Incidence and clinical correlates of anger attacks in Chinese patients with obsessive-compulsive disorder - Ying-ying Zhang; Heng-fen Gong; Xiao-li Zhang; Wen-juan Liu; Hai-yan Jin; Fang Fang; Sophie Schneider; Elizabeth McIngvale; Chen-cheng Zhang; Wayne K. Goodman; Xi-rong Sun; Eric A. Storch (Journal of Zhejiang University-SCIENCE B, 2019)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Trichoderma harzianum-induced resistance against Fusarium oxysporum involves regulation of nuclear DNA content, cell viability and cell cycle-related genes expression in cucumber roots - Shuang-Chen Chen; Hong-Jiao Zhao; Zhong-Hong Wang; Cai-Xia Zheng; Pu-Yan Zhao; Zhi-Hua Guan; Hai-Yang Qin; Ai-Rong Liu; Xiao-Min Lin; Golam-Jalal Ahammed (European Journal of Plant Pathology, 2017)

EGFL7-overexpressing epidermal stem cells promotes fibroblast proliferation and migration via mediating cell adhesion and strengthening cytoskeleton - Rong-Hua Yang; Shao-Hai Qi; Shu-Bin Ruan; Ze-Peng Lin; Yan Lin; Feng-Gang Zhang; Xiao-Dong Chen; Ju-Lin Xie (Molecular and Cellular Biochemistry, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

A preliminary study on the potential value of a novel integrated aquaculture system on water purification - Li-hong Chen; Rong-lian Xing; Ai-li Jiang; Li Teng; Chang-hai Wang (Aquaculture International, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Hydrogen sulfide alleviates zinc toxicity by reducing zinc uptake and regulating genes expression of antioxidative enzymes and metallothioneins in roots of the cadmium/zinc hyperaccumulator Solanum nigrum L. - Xiang Liu; Juan Chen; Guang-Hui Wang; Wen-Hua Wang; Zhi-Jun Shen; Mei-Rong Luo; Gui-Feng Gao; Martin Simon; Kabir Ghoto; Hai-Lei Zheng (Plant and Soil, 2016)

Preparation of Bacterial Cellulose/Inorganic Gel of Bentonite Composite by In Situ Modification - Bo Wang; Gao-xiang Qi; Chao Huang; Xiao-Yan Yang; Hai-Rong Zhang; Jun Luo; Xue-Fang Chen; Lian Xiong; Xin-De Chen (Indian Journal of Microbiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

DNA methylation analysis of sterile and fertile CMS-C hybrids and their parents in maize - Bo Chen; Yan Zhang; Yanli Lu; Jing Wang; Suzhi Zhang; Hai Lan; Tingzhao Rong; Moju Cao (Journal of Plant Biochemistry and Biotechnology, 2016)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Bacteriological and virulence study of a Mycobacterium chimaera isolate from a patient in China - Guan Liu; Su-Ting Chen; Xia Yu; Yu-Xun Li; Ying Ling; Ling-Ling Dong; Su-Hua Zheng; Hai-Rong Huang (Antonie van Leeuwenhoek, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Analysis on the association between PPARα/γ polymorphisms and lipoprotein(a) in a Chinese Han population - Hui-Jian Xie; Bo Hai; Ming Wu; Qiu Chen; Meng-Meng Liu; Chen Dong; Zhi-Rong Guo (Molecular Genetics and Genomics, 2014)

Overexpression of TFAM Protects 3T3-L1 Adipocytes from NYGGF4 (PID1) Overexpression-Induced Insulin Resistance and Mitochondrial Dysfunction - Chun-Mei Shi; Guang-Feng Xu; Lei Yang; Zi-Yi Fu; Ling Chen; Hai-Long Fu; Ya-Hui Shen; Lu Zhu; Chen-Bo Ji; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2013)

Aluminum tolerance of wheat does not induce changes in dominant bacterial community composition or abundance in an acidic soil - Chao Wang; Xue Qiang Zhao; Rong Fu Chen; Hai Yan Chu; Ren Fang Shen (Plant and Soil, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Construction of multiple shRNAs expression vector that inhibits FUT1 gene expression and production of the transgenic SCNT embryos in vitro - Jian-wen Chen; Yu Zhang; Yuan-liang Zhang; Chao Wei; Xing Liu; Na-ru Zhou; Qing Jia; Yun-sheng Li; Xiao-rong Zhang; Yun-hai Zhang (Molecular Biology Reports, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Establishment of SYBR green-based qPCR assay for rapid evaluation and quantification for anti-Hantaan virus compounds in vitro and in suckling mice - Fei Wei; Jin-lin Li; Jia-xin Ling; Liang-Jun Chen; Ning Li; Yuan-Yuan Liu; Fan Luo; Hai-Rong Xiong; Wei Hou; Zhan-Qiu Yang (Virus Genes, 2013)

Episodic orogeny deduced from coeval sedimentary sequences in the foreland basin and its implication for uplift process of Longmen Mountain, China - Yong Li; De-chen Su; Rong-jun Zhou; Hai-bing Li; Alexander L. Densmore; Liang Yan; Zhao-kun Yan (Journal of Mountain Science, 2013)

Biomass accumulation and partitioning, photosynthesis, and photosynthetic induction in field-grown maize (Zea mays L.) under low- and high-nitrogen conditions - Jun-Wen Chen; Zhi-Qing Yang; Ping Zhou; Mei-Rong Hai; Tian-Xiang Tang; Yan-Li Liang; Tong-Xin An (Acta Physiologiae Plantarum, 2013)

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Cloning, Characterization and Functional Analysis of a Phenylalanine Ammonia-lyase Gene (FtPAL) from Fagopyrum tataricum Gaertn - Cheng Lei Li; Yue Chen Bai; Hui Chen; Hai Xia Zhao; Ji Rong Shao; Qi Wu (Plant Molecular Biology Reporter, 2012)

Genetic characterization of a new subtype of Hantaan virus isolated from a hemorrhagic fever with renal syndrome (HFRS) epidemic area in Hubei Province, China - Jin-lin Li; Jia-xin Ling; Dong-ying Liu; Jing Liu; Yuan-yuan Liu; Fei Wei; Fan Luo; Wen Chen; Yi-hui Zhang; Hai-rong Xiong; Wei Hou; Zhan-qiu Yang (Archives of Virology, 2012)

Experimental study on the effect of waves on netting panels at a range of angles to the wave direction - Wei-hua Song; Zhen-lin Liang; Rong Wan; Fen-Fang Zhao; Kinoshita Takeshi; Liu-yi Huang; Jia-zhi Ma; Bo-hai Chen (Fisheries Science, 2012)

Synthesis of novel 6-triazologlycolipids via click chemistry and their preliminary cytotoxicity assessments - Hai-Lin Zhang; Xiao-Peng He; Li Sheng; Yuan Yao; Wei Zhang; Xiao-Xin Shi; Jia Li; Guo-Rong Chen (Molecular Diversity, 2011)

Isolation of a buprofezin co-metabolizing strain of Pseudomonas sp. DFS35-4 and identification of the buprofezin transformation pathway - Kai Chen; Xiao-Mei Liu; Rong Li; Yuan Liu; Hai Hu; Shun-Peng Li; Jian-Dong Jiang (Biodegradation, 2011)

Plantagiolide F, a minor withanolide from Tacca plantaginea - Jun-Yun Yang; Chang-Xiang Chen; Rong-Hua Zhao; Xiao-Jiang Hao; Hai-Yang Liu (Natural Product Research, 2011)

Diversity and Antimicrobial and Plant-Growth-Promoting Activities of Endophytic Fungi in Dendrobium loddigesii Rolfe - Xiao Mei Chen; Hai Ling Dong; Ke Xing Hu; Zhi Rong Sun; Juan Chen; Shun Xing Guo (Journal of Plant Growth Regulation, 2010)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)